Hematology : landmark papers of the twentieth century - Lichtman, Marshall A.; Spivak, Jerry L. (Academic Press, 2000)
This book is a centennial volume celebrating the enormous progress made in hematology in the 20th century. It is edited by Marshall Lichtman, a distinguished senior hematologist, past president of the American Society of Hematology, and co-editor of the leading text in the field. Hematology is a compendium, with commentaries, of the most important papers published in the field from 1900-1999. The book will be useful for reference--many of the older papers can no longer be found in most libraries, yet are still referred to in current publications, especially review articles--as well as teaching. The Editor and a team of associate editors have included the most important papers covering eight categories: anemia; phagocytic cells; platelets; coagulation and thrombosis; lymphocytes and immune disorders; transfusion medicine; hematologic malignancies and therapeutics; and laboratory developments. Each paper is accompanied by a 1-2 page commentary explaining its impact, and references to the developments that resulted. Key Features * Contains 86 landmark articles from the last 100 years of research in clinical hematology * Includes expert commentaries discussing the impact of each article * Cites approximately 1000 preceding or subsequent articles of consequence in the commentaries * Includes the English translations of nine articles originally published in other languages * Provides easy access to several papers that may no longer be found in libraries.